Microgravity and Cardiovascular Health in Astronauts: A Narrative Review - John Azariah; Umberto Terranova (Health Science Reports)
ABSTRACT Background Space exploration has become a major interest for scientific and medical research. With increasing duration and frequency of manned space missions, it is crucial to understand the impact of microgravity on the cardiovascular health of astronauts. We focus on this relationship by reviewing literature that explores how microgravity affects several hemodynamic parameters and cardiovascular biomarkers. Methods We conducted a search updated to November 2024 across several databases, including PubMed, Cochrane Library, ESA, NASA and DLR, using relevant MeSH terms and selection criteria. Results The 22 selected articles detail how microgravity impacts the cardiovascular system and its adaptations. We identify some clear patterns, such as loss of ventricular mass and increased QT intervals (corrected for heart rate) indicating increased risk of arrhythmias. Our analysis confirms that head‐down tilt is an accurate analog of microgravity. Conclusions While a direct link between microgravity and cardiovascular disease, such as coronary heart disease and myocardial infarction, remains elusive, the documented physiological changes pose a potential threat to the astronauts' health. We suggest that future research focus on long‐term effects, particularly on female subjects.